Monotheistic Ontology With an Emphasis on the Story of Jesus in the Holy Books - Fatemeh Khiveh; Omid Asemani; Sedigheh Ebrahimi; Seyed Ziaeddin Tabei , MD (AL-IKHSAN: Interdisciplinary Journal of Islamic Studies, 2025)
From the point of view of the philosophers, existence is original, and nature is a garment on the stature of existence Monotheistic religions, especially Islam, emphasize the necessity of human knowledge, and they introduce human knowledge as a way to achieve God's knowledge. God is an absolute and pure existence, so he will not dissolve in a place or a person. Christ was able to take on divine nature and become the Word of God with divine approval. This understanding highlights evidence of God's existence across both realms. What is certain is that monotheistic religions share closer ties than atheistic schools, suggesting that human beings and the fate of religious people are tied together more than in other societies. Establishing scholarly relationships among followers of divine religions requires clear and precise knowledge. Comparative studies between religions are one of the ways to create peace, coexistence, and rapprochement between the followers of religions. This study used an analytical and descriptive methodology. Our research framework is predicated on a comprehensive description and analysis of textual content, coupled with the extrapolation of verses, narratives, and authoritative sources from libraries to enhance our inquiry.  .